Physicochemical analysis of selenium nanoparticles synthesis via pomegranate peel extracts approach: Cytotoxic impact on MCF7 cell line - Ahmed, Zahraa Mohammed; Ahmed, Mais Emad (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Over the past decade, sustainable bimetallic nanoparticles (NPs) have attracted significant scientific attention. However, challenges related to synthesis efficiency and environmental impact remain major concerns. In this study, we present the green synthesis of bimetallic selenium nanoparticles (SeNPs) using pomegranate peel extract (PPE) as a natural, eco-friendly reducing and stabilizing agent. The synthesized nanoparticles were thoroughly characterized using Fourier-transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), ultraviolet-visible (UV–Vis) spectroscopy, transmission electron microscopy (TEM), and energy-dispersive X-ray (EDX) analysis, confirming their successful formation, uniform morphology, and homogeneous distribution. The biosynthesized SeNPs demonstrated potent in vitro anticancer activity against the human breast cancer cell line (MCF-7), exhibiting a half-maximal inhibitory concentration (IC₅₀) of 11 μg/mL, while remaining non-toxic and biocompatible at lower concentrations. These findings highlight the significant biomedical potential of PPE-mediated bimetallic SeNPs as safe and effective anticancer agents. Overall, this green biosynthetic approach provides a sustainable and efficient alternative to conventional chemical synthesis methods for producing functional metal oxide nanoparticles.